Transition-metal-free and visible-light-mediated desulfonylation and dehalogenation reactions: Hantzsch ester anion as electron and hydrogen atom donor - Heredia, Micaela Denise (2020)
Novel approaches for N- and O-desulfonylation under room temperature (rt) and transition-metal-free conditions have been developed. The first methodology involves the transformation of a variety of N-sulfonyl heterocycles and phenyl benzenesulfonates to the corresponding desulfonylated products in good to excellent yields using only KOtBu in dimethyl sulfoxide (DMSO) at rt. Alternately, a visible light method has been used for deprotection of N-methyl-N-arylsulfonamides with Hantzsch ester (HE) anion serving as the visible-light-absorbing reagent and electron and hydrogen atom donor to promote the desulfonylation reaction. The HE anion can be easily prepared in situ by reaction of the corresponding HE with KOtBu in DMSO at rt. Both protocols were further explored in terms of synthetic scope as well as mechanistic aspects to rationalize key features of desulfonylation processes. Furthermore, the HE anion induces reductive dehalogenation reaction of aryl halides under visible light irradiation.